Photoluminescent layered Y/Er silicates - Kostova, Mariya H. (2008)
The synthesis of new layered rare-earth silicates K3[Y1-aEraSi3O8(OH)2] (AV-22 materials) has been reported. The photoluminescence properties of Y/Er-AV-22 and the material resulting from its thermal degradation, K3[Y1-aEraSi3O9] (Y/Er-AV-23), have been studied and compared. Both materials have a similar chemical makeup and structures sharing analogous building blocks, hence providing a unique opportunity for rationalising the evolution of the photoluminescence properties of lanthanide silicates across dimensionality.